1999
DOI: 10.1063/1.123280
|View full text |Cite
|
Sign up to set email alerts
|

Detection of copper contamination in silicon by surface photovoltage diffusion length measurements

Abstract: Surface photovoltage minority carrier lifetime/diffusion length analysis of copper contaminated silicon was performed. It was observed that copper and copper associated defects degrade minority carrier lifetime more in n-type than in p-type silicon. This finding is explained by analysis of copper related defect levels identified by other deep level transient spectroscopy studies. In copper contaminated p-type silicon, an optical or thermal activation procedure significantly degrades the diffusion length. A pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 16 publications
0
55
0
Order By: Relevance
“…Early contributions attributed Cu-LID to the dissociation of a recombination inactive pure copper complex, which was long presumed to be Cu s Cu i pair, and the subsequent formation of highly recombination active Cu s complexes. 14,30 However, this reaction does not explain the aforementioned decrease of Cu þ i concentration during light-soaking. Moreover, DLTS studies on intentionally Cu contaminated material revealed the existence of two acceptor energy states located at E v þ 0:41…0:45 eV [31][32][33][34] and E c À 0:16 eV 24 and a donor energy level at E v þ 0:22 eV, 24,35 which were later associated with the substitutional copper defect.…”
Section: Comparison With Literature Data and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early contributions attributed Cu-LID to the dissociation of a recombination inactive pure copper complex, which was long presumed to be Cu s Cu i pair, and the subsequent formation of highly recombination active Cu s complexes. 14,30 However, this reaction does not explain the aforementioned decrease of Cu þ i concentration during light-soaking. Moreover, DLTS studies on intentionally Cu contaminated material revealed the existence of two acceptor energy states located at E v þ 0:41…0:45 eV [31][32][33][34] and E c À 0:16 eV 24 and a donor energy level at E v þ 0:22 eV, 24,35 which were later associated with the substitutional copper defect.…”
Section: Comparison With Literature Data and Discussionmentioning
confidence: 99%
“…6,7 This phenomenon is referred to as copper-related light-induced degradation (Cu-LID), and it has been suggested to arise from increased bulk recombination [8][9][10] caused by copper precipitation 11,12 or substitutional copper complexes. [13][14][15] Nevertheless, the recombination mechanisms at Cu-LID defects still remain unclear, and the current literature information is lacking in an accurate parametrization of the recombination activity of such defects. Therefore, it is important to determine the recombination parameters of Cu-LID defects in order to quantify their effect on minority carrier lifetime and predict their impact on the overall solar-cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…The Cu-LID has been confirmed to originate from bulk recombination, 5 which is proposed to be caused by copper precipitation 7 or substitutional copper release through copper complex dissociation during illumination. 8,9 The formed defects have been found to be stable at 200 C in wafers with initial interstitial copper concentration of 10 14 cm À3 . 10 In addition to copper defects, the involvement of boron and oxygen in the formation of a metastable recombinationactive defect (BO-LID) has been extensively reported as the major cause of degradation in low-resistivity boron-doped Czochralski (Cz) silicon.…”
mentioning
confidence: 99%
“…4 The recombination lifetime method is, therefore, not suitable as such for the detection of trace Cu contamination. Nevertheless, Henley et al 5,6 observed recently using surface photovoltage method that in copper contaminated samples optical or thermal activation decreases the diffusion length. They proposed that extended substitutional defects are formed as a result of the activation process.…”
mentioning
confidence: 99%